The Yeast RSC Chromatin-Remodeling Complex Is Required for Kinetochore Function in Chromosome Segregation - Hsu, Jing-mei (American Society for Microbiology, 2003)
The accurate segregation of chromosomes requires the kinetochore, a complex protein machine that assembles onto centromeric DNA to mediate attachment of replicated sister chromatids to the mitotic spindle apparatus. This study reveals an important role for the yeast RSC ATP-dependent chromatin-remodeling complex at the kinetochore in chromosome transmission. Mutations in genes encoding two core subunits of RSC, the ATPase Sth1p and the Snf5p homolog Sfh1p, interact genetically with mutations in genes encoding kinetochore proteins and with a mutation in centromeric DNA. RSC also interacts genetically and physically with the histone and histone variant components of centromeric chromatin. Importantly, RSC is localized to centromeric and centromere-proximal chromosomal regions, and its association with these loci is dependent on Sth1p. Both sth1 and sfh1 mutants exhibit altered centromeric and centromere-proximal chromatin structure and increased missegregation of authentic chromosomes. Finally, RSC is not required for centromeric deposition of the histone H3 variant Cse4p, suggesting that RSC plays a role in reconfiguring centromeric and flanking nucleosomes following Cse4p recruitment for proper chromosome transmission.